An exemplum Play by Plautus - Tatyana A. Bobrovnikova (Hypothekai, 2018)
The article is devoted to Plautus’ comedy «The Captives». Plautus, like other Roman comedy dramatists, never acted as a teacher to the audience. This completely did not correspond to the traditions of the Roman Republican Theater, which was purely entertaining. However, the author proves that, among Plautus’ works, the play under consideration is unique both in terms of the plot and techniques. Plautus himself singles out this comedy and claims that it is not written for the entertainment of the audience, like all the rest, but with the aim of improving their morals, that is, Plautus only once appears in the role of the teacher, which is so uncharacteristic of the Roman scene.The task of our article is to find out what Plautus wanted to teach his compatriots. We come to the conclusion that the subject of the comedy is attitude towards slaves. From the very beginning, the poet sharply condemns the slave trade. The play was staged during the Second Punic War or immediately after it. Hundreds of Romans were captured and turned into slaves in foreign lands. The poet plays on this moment, tries to arouse pity for the slaves in the audience, reminding of their friends and relatives’ fate. He keeps repeating – today you are free, and tomorrow you can become slaves. The protagonist says, “Human fortune moulds and fashions just as she wills. Myself, who was a free man she has made a slave, from the very highest the very lowest. I, who was accustomed to command, now obey the mandates of another. And indeed, if I meet with a master just such as I proved the ruler in my own household, I shall not fear that he will rule me harshly or severely... As free a man was I till lately as your son. As much did a hostile hand deprive me of my liberty as him of his. As much is he a slave among my people, as I am now a slave here with yourself. There is undoubtedly a God, who both hears and sees the things which we do. Just as you shall treat me here, in the same degree will he have a care for him. To the welldeserving will he show favour, to the illdeserving will he give a like return. As much as you lament your son, so much does my father lament me.” Thus, the deity itself, according to Plautus, monitors the attitude of the master to the slaves and punishes him for the harm done. We believe that a very interesting point is that many of the places in this comedy closely echo with the political speeches of the famous Plautus’ contemporary, Cato the Elder. An analysis of these places leads the author to the conclusion that Plautus’ comedy is of agonistic character. With the help of the art, Plautus strives to demolish the arguments of the famous politician